Planning of Risks of Implementation of Projects of Public-private Partnership - Ulyana Dmitrievna Kondratieva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
This article analyzes the mechanism of planning risks that may arise during the implementation phase of the PPP project, the main stages of planning risks from the public partner and the private partner of the project. Also the article characterized the value of the information system in the implementation of procedures for planning risks of PPP projects and subsequent management.